Improving skills retention after advanced structured resuscitation training: A systematic review of randomized controlled trials. (May 2019) - Au, Kelly; Lam, Darren; Garg, Nitan; Chau, Anthony; Dzwonek, Agata; Walker, Benjamin; Tremblay, Luc; Boet, Sylvain; Bould, M. Dylan
Abstract: Aims: To systematically evaluate the literature on interventions that improve skills retention following advanced structured resuscitation training programs designed for healthcare professionals. Methods: A systematic review of MEDLINE, EMBASE, CENTRAL, CINAHL, PsycINFO, ERIC, and Scopus was performed. Only randomized controlled trials investigating skills retention following advanced structured resuscitation training programs for healthcare professionals between inception to November 21, 2018 were included. Publications that assessed only knowledge acquisition were excluded. Relevant data from included studies were extracted and study quality was critically appraised, both independently and in duplicate by multiple reviewers. The risk of bias was assessed with the Cochrane Risk of Bias tool and the Medical Education Research Study Quality Instrument (MERSQI). Due to significant clinical heterogeneity in SRT training, study designs and interventions, a qualitative synthesis was used to summarize findings. Main results: Sixteen studies, with a combined total of 1192 participants, were included in the final analysis. The majority of studies were conducted in North America and involved trainees or novice learners. ACLS was the most extensively studied, followed by NRP, ALS, and ATLS. Skills retention at 6 months was the most commonly used primary endpoint assessed using a simulated resuscitation checklist with either an adopted or created assessment tool. Most studies demonstrated a positive impact on skills retention when an interactive intervention or simulation was used. However, merely having a high-fidelity mannequin alone for simulation was found to have minimal effect on skills retention in the absence of other changes in content delivery. Booster sessions were found to be minimally effective in reinforcing long-term skills retention; however, most studies examining this intervention had small sample sizes and were underpowered. Conclusions: Simulation-based interventions, refresher courses and adjustments to the content delivery of advanced structured resuscitation training courses were found to have the greatest impact on skills retention. However, due to significant heterogeneity and methodological flaws in the available studies, no definitive conclusions can be made regarding other interventions. Overall, there is a paucity of skills retention research and further high-quality randomized controlled trials are needed to determine the optimal intervention and design for resuscitation training that would maximize skills retention.